Responses of CO2 emissions and soil microbial community structures to organic amendment in two contrasting soils in Zambia - Toru Hamamoto; Nhamo Nhamo; David Chikoye; Ikabongo Mukumbuta; Yoshitaka Uchida (Scientific Reports, 2022)
Abstract In sub-Saharan Africa, efforts have been made to increase soil carbon (C) content in agricultural ecosystems due to severe soil degradation. The use of organic materials is a feasible method for recovering soil organic C; however, the effects of organic amendments on soil microbial communities and C cycles under C-limited soil conditions are still unknown. In this study, we conducted field experiments in Zambia using organic amendments at two sites with contrasting C content. At both sites, temporal changes in soil carbon dioxide (CO2) emissions and prokaryotic community structures were monitored during the crop growing season (126 days). The organic amendments increased CO2 emissions and prokaryotic abundance at the Kabwe site, whereas no direct impacts were observed at the Lusaka site. We also observed a larger temporal variability in the soil microbial community structure at Kabwe than that at Lusaka. These contrasting results between the two soils may be due to the microbial community stability differences between each site. However, as organic amendments have considerable potential to enhance microbial abundance and consequently sequester C at the Kabwe site, site-specific strategies are required to address the issues of soil C depletion in drylands.